Prenatal care in the municipality of quixadá: a descriptive study - Maria Eudênia Oliveira Barros (Online Brazilian Journal of Nursing, 2012)
ntroduction: Prenatal care is essential to promote the health/well - being of the mother and the conceptus . Aim: The objective was to assess the prenatal care offered in the Basic Health Units in the city of Quixadá. Methods: A descriptive study was carried out on 73 women participants. A form was used to collect data. Results: Prenatal consultations involve the basic procedures related to pregnancy only. There is a deficiency in respect of health education, as 82.2 percent of the participan ts said they had never participated in such activity. The main laboratory tests recommended by the Ministry of Health (MH) were ordered for the pregnant women. By analyzing the prenatal cards and forms, it was found that 100 percent were incomplete or outd ated. Conclusion: The study showed that the prenatal care offered to pregnant women is below the standards set by the MH, which affects the quality of care.